The role of government disclosure of carbon emissions in including environmental allocations in the federal budget (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to know the role of government disclosure of carbon emissions in including environmental allocations in the federal general budget, as well as knowing the level of disclosure of carbon emissions in the Board of Directors’ reports and the annual financial reports of the research sample represented by the Midland Oil Company.  To achieve this goal, the researchers analyzed the content of the Board of Directors’ report, the reports attached to it, and the annual financial reports to determine the level of disclosure of carbon emissions. As for the role of government disclosure of carbon emissions information in including environmental allocations, a five-point questionnaire was designed according to a Likert scale and distributed to academics. Those specializing in accounting, as well as those working in the Bureau of Financial Supervision.  The results of the study indicated that the disclosure rate is low and does not reach the level of information that can be relied upon in understanding the general situation regarding carbon emissions or making decisions that can reduce the volume of emissions. The results also indicated that there is a large and important role for the disclosure of carbon emissions in including environmental allocations in the federal general budget, as the process of including environmental allocations in the budget can contribute to enhancing environmental disclosure in general, and disclosure of carbon emissions in particular.The most important conclusions that I reached were that there is a relationship between disclosure of carbon emissions and the federal general budget, as environmental allocations in the budget also enhance carbon disclosure in particular and environmental disclosure in general, since these allocations are followed by disclosure of the extent of implementation of the government plan and thus the extent of achieving the goals associated with it. The researchers recommended that the Iraqi government should accelerate the adoption of a carbon accounting model whose core is to collect information about carbon emissions and disclose them based on international standards and rules, and whose goals are consistent with emissions reduction goals at the international level.